SOCIAL PROCESSES IN CHAGATAI ULUS (International journal of artificial intelligence, 2025)
This article analyzes the socio-economic history of the Chagatai tribe, land relations and tax system during the Mongol period. After the death of Genghis Khan, the role of Mahmud Yalavoch in Movarunnahr, the introduction of new forms of taxation (for example, "kalon", "kopchur", "tamg'a") and land reforms are shown. The Mongols' policy of tax collection and land management, and the plight of artisans and peasants, are discussed. Also discussed is the decline in trade and the derailment of money circulation. The article contains important information about the socio-economic system of the Mongol period.